DAMPAK PENGGUNAAN GADGET SECARA BERLEBIHAN TERHADAP MOTIVASI BELAJAR SISWA KELAS IV SDN 1 KANDANGAN - Meryta Ivanka; A.Y Soegeng Ysh; M. Yusuf Setia W (STKIP Subang, 2025)
This study examines the impact of excessive gadget use on the learning motivation of fourth-grade students at SDN 1 Kandangan. The overuse of gadgets among elementary school students can lead to various negative effects, including physical, psychological, and social consequences. Physically, excessive gadget use may cause sleep disturbances, vision problems, and a lack of physical activity, which can affect children’s health and fitness. Psychologically, students may experience decreased concentration, emotional instability, and gadget addiction, leading to a decline in motivation and enthusiasm for learning. Socially, excessive gadget use reduces students’ interactions with peers and family, which affects their social and emotional development. This research employed a qualitative descriptive approach with data collection techniques such as direct observation, in-depth interviews with students, teachers, and parents, and documentation to obtain a comprehensive picture of the effects of gadget overuse. Observations were conducted in the school environment to assess gadget usage patterns and behavioral changes, while interviews explored students’ learning experiences and the supervision efforts by schools and families. The results showed that uncontrolled gadget use had a significant negative impact on students’ learning motivation, particularly in reducing focus, discipline, and interest in learning. However, with proper management and supervision from teachers and parents, gadgets can also serve as effective interactive learning tools that enhance motivation and creativity. This study recommends establishing healthy gadget usage schedules, selecting educational content, and strengthening coordination between schools and parents to ensure that gadgets are used productively to support a healthy, engaging, and effective learning process